Effect of high-temperature heat treatment on mechanical properties and microstructure of CoCrNi medium-entropy alloy formed by laser powder bed fusion - Laixia Yang; Mengjia Yang; Yanze Zhang; Qidong Xie; Longbo Zhang; Zhen Chen; Hang Su (Journal of Materials Research and Technology)
Laser additive manufacturing (LAM) of high/medium-entropy alloys (H/MEA) possesses considerable industrial promise. In this study, laser powder bed fusion (L-PBF) was employed to fabricate a CoCrNi MEA with excellent strength-ductility synergy. The investigation delves into the microstructural evolution, mechanical properties, and the influence of microstructure on mechanical performance after annealing at 1200 °C for 1, 2, and 4 h. This research addresses deficiencies in traditional processes and native laser additive manufacturing of CoCrNi. Testing and analysis reveal a notable increase in elongation after high-temperature annealing, accompanied by a trend towards equiaxed grain morphology with increasing fractions of recrystallization and annealing twin boundaries, and a gradual reduction in geometric dislocation density. Alterations in grain morphology, dislocation density, fractions of recrystallization, and grain boundary misorientation significantly impact mechanical properties. The findings demonstrate a marked enhancement in elongation after high-temperature annealing of CoCrNi MEA, suggesting promising applications in environments requiring high ductility.